2016
DOI: 10.1055/s-0036-1593774
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Transvaginal Ultrasonography, Hysteroscopy and Uterine Curettage in Evaluating Endometrial Pathologies

Abstract: To evaluate the accuracy of transvaginal ultrasonography, hysteroscopy and uterine curettage in the diagnosis of endometrial polyp, submucous myoma and endometrial hyperplasia, using as gold standard the histopathological analysis of biopsy samples obtained during hysteroscopy or uterine curettage. Cross-sectional study performed at the Hospital Universitário de Brasília (HUB). Data were obtained from the charts of patients submitted to hysteroscopy or uterine curettage in the period from July 2007 to July 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 26 publications
4
21
1
6
Order By: Relevance
“…A limitation of ultrasonography imaging is that it does not allow biopsy for diagnostic confirmation. In view of this, a recent study concluded that ultrasonography presents a barrier to the diagnosis of endometrial pathologies and that a biopsy should be performed under direct visualization by hysteroscopy …”
Section: Discussionmentioning
confidence: 99%
“…A limitation of ultrasonography imaging is that it does not allow biopsy for diagnostic confirmation. In view of this, a recent study concluded that ultrasonography presents a barrier to the diagnosis of endometrial pathologies and that a biopsy should be performed under direct visualization by hysteroscopy …”
Section: Discussionmentioning
confidence: 99%
“…Polyps were confirmed in up to 28% of symptomatic postmenopausal women 2 . In 134 patients who underwent hysteroscopy, the procedure revealed a diagnostic accuracy higher than 90% for all the diseases evaluated, while transvaginal ultrasonography showed an accuracy of 65.9% for polyps 10 . Higher sensitivty up to 89% and specificity up to 87% is obtained when using color-flow sonography and detecting one feeding blood vessel 11 .…”
Section: Discussionmentioning
confidence: 94%
“…This study comprised 789 premenopausal women and had 94% sensitivity and 95% specificity of hysteroscopical procedure, while transvaginal ultrasound had sensitivity 54% and specificity 80% for detection endometrial polyps 12 . Ideally, after initial investigation with transvaginal ultrasonography, guided biopsy of the lesion should be performed by hysteroscopy, whenever necessary, in order to improve the diagnostic accuracy and subsequent clinical management 10 . There is a chance for spontaneous regression of polyps, higher for smaller ones 13 .…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that after initial investigation with transvaginal ultrasonography, guided biopsy of the lesion should be performed by hysteroscopy when-ever necessary in order to improve the diagnostic accuracy and subsequent clinical management [17].…”
Section: Discussionmentioning
confidence: 99%